2001
DOI: 10.1111/j.1553-2712.2001.tb01117.x
|View full text |Cite
|
Sign up to set email alerts
|

When the Safety Net Is Unsafe Real‐time Assessment of the Overcrowded Emergency Department

Abstract: Abstract. Although much work has been done evaluating causes for increased demand for emergency department (ED) services, few ways are available to help determine that an individual ED is overcrowded. Four calculations are proposed using real-time data for accurately diagnosing an ED with potential for failing both as a safety net and as a source for quality health care. The bed ratio (BR) accounts for the number of patients in relation to the available treatment spaces. The BR is obtained by adding the curren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(50 citation statements)
references
References 18 publications
2
47
0
1
Order By: Relevance
“…Threshold policies are abstractions from more complex workload measures of ED crowding proposed in the emergency medicine literature, which account for additional factors such as staffing and patient severity [Reeder and Garrison 2001, Bernstein et al 2003, Epstein and Tian 2006. Recent research shows that ED occupancy predicts overcrowding as well as these workload measures [Hoot et al 2007] and correlates well with the staff's perception of overcrowding [McCarthy et al 2008].…”
Section: Threshold Policiesmentioning
confidence: 99%
“…Threshold policies are abstractions from more complex workload measures of ED crowding proposed in the emergency medicine literature, which account for additional factors such as staffing and patient severity [Reeder and Garrison 2001, Bernstein et al 2003, Epstein and Tian 2006. Recent research shows that ED occupancy predicts overcrowding as well as these workload measures [Hoot et al 2007] and correlates well with the staff's perception of overcrowding [McCarthy et al 2008].…”
Section: Threshold Policiesmentioning
confidence: 99%
“…[6][7][8] Conceptual models such as the input-throughputoutput model, 9 the Fields chaos model, 10 and the ED Cardiac Analogy Model 11 have been introduced in an effort to understand the factors of overcrowding and their mechanisms. Even the definition of overcrowding is problematic, 12 giving rise to various proposals for measuring ED crowding [13][14][15] and developing consensus on indices of overcrowding. 16 More recently, the National ED Overcrowding Study has demonstrated a simple measure of ED overcrowding across multiple institutions.…”
mentioning
confidence: 99%
“…Some built mathematical models to define when an ED is crowded [7][8][9]. Yet, in some of them there was a mismatch between the definition of overcrowding according to these calculations, and the perception of overcrowding among the ED medical and nursing staff [7,10]. In others, the Emergency department work index (EDWIN) has been shown to be a strong predictor of ambulance diversion, and also to correlate well with staff perception of crowding [8,11].…”
Section: Discussionmentioning
confidence: 99%
“…Some built mathematical models to define when an ED is crowded [7][8][9]. Yet, in some of them there was a mismatch between the definition of overcrowding according to these calculations, and the perception of overcrowding among the ED medical and nursing staff [7,10].…”
Section: Discussionmentioning
confidence: 99%